PENGARUH GROWTH OPPORTUNITY, LEVERAGE, DAN PENGELUARAN MODAL TERHADAP CASH HOLDING PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Desi Lita Aryani; Yenny Ernitawati; Hilda Kumala Wulandari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Cash holding is a company strategy for maintaining liquidity. This research aims to analyze the influence of Growth Opportunity, Leverage and Capital Expenditure on Cash Holding. This research uses a quantitative approach with comparative methods. The research population includes 56 companies in the consumer goods sector listed on the Indonesia Stock Exchange (BEI) in the 2021-2023 period, with a total sample of 168 data. The data analysis techniques used include descriptive statistics, normality tests, and hypothesis tests carried out with the help of SPSS software. The research results show that Growth Opportunity, Leverage, and Capital Expenditure have a significant effect on Cash Holding.